Factors Influencing Antenatal Care Services Utilization in Primary Health Care Centers in the Second Sector of Basra City Center: Faktor-faktor yang Mempengaruhi Pemanfaatan Pelayanan Antenatal Care di Puskesmas di Sektor Kedua Pusat Kota Basra - Hasan, Marwa Abdul-Satar; Abdul-Qader, Rasha Ahmed; Obaid, Hanadi Lazim (Universitas Muhammadiyah Sidoarjo, 2025)
This cross-sectional study was conducted to assess the factors influencing the utilization of ANC services. The total sample consisted of 400 cases with a previous history of pregnancy attending ANC for less than one year, was collected from 15 PHCCs in the second sector of Basra city center, through face-to-face interviews and the use of a questionnaire format during the study period which extended from the beginning of February to the end of July 2018. The results of the present study showed that (31.5%) of the participants’ ages were between 20-25 years old. About two-thirds of the studied women (68.5%) lived in the family home of their husbands; (69.0%) of them had a partner of 1–3. Both studied women, and their husbands had the highest percentage of intermediate education, (28.5%) and (29.5%) respectively. The majority of women (93.7%) were housewives, and most of their husbands were self-employed (67.3%). The highest percentage of participants (66.0%) lived in families composed of seven and above members. There were (89.5%) of women had no history of stillbirth. It was suggested that more government efforts be made to target less educated women and to inform them of the advantages of using antenatal care, this proposal also needs to include their husbands and improve family planning services. Government policy should help increase the spread of the media among mothers. Provide ultrasonic examination services (SONAR) in all primary health care centers and finally, further research should be obtained to include both urban and rural areas. Highlights: Majority were housewives, aged 20–25, with intermediate education level. Most lived in large families, husband's home, with 1–3 children. Recommend education, media access, SONAR services, and broader research coverage. Keywords: Factors, Antenatal Care Services, in Primary Health Care Centers.